Cell-cycle dependence of induced hemoglobin synthesis in Friend erythroleukemia cells temperature-sensitive for growth. - Conkie, D (1981)
Friend erythroleukemia cells temperature-sensitive (ts) for growth have been used to study the cell-cycle dependence of erythroid differentiation. ts cells accumulated hemoglobin in response to inducer when replicating optimally at permissive temperatures. However, when arrested in the G1 phase of the cell cycle at a nonpermissive temperature, ts cells did not accumulate hemoglobin or globin mRNA nor did they differentiate terminally. Under these conditions, the viability of ts cells treated with inducer at the nonpermissive temperature remained high (70% of that of cells induced at the permissive temperature) as judged by cloning experiments. Total RNA and protein synthesis of G1 cells treated with inducer was 44-48% of that of randomly proliferating induced cells, in contrast to thymidine incorporation into DNA which decreased to 2% of that of cells replicating at the permissive temperature. Furthermore, G1 ts cells treated with inducer accumulated hemoglobin when released from growth arrest at the permissive temperature in the presence (but not in the absence) of inducer. These results are consistent with a requirement for a cell cycle-dependent event prior to commitment to differentiation.